Validation and Application of a Simplified Approach for Seismic Performance Evaluation of Steel CBFs - Leonard Doci; Rosario Montuori; Elide Nastri; Vincenzo Piluso; Paolo Todisco (Metals)
This paper validates a simplified approach for evaluating the seismic performance of concentrically braced frames (CBFs). The method, based on a performance-based design, defines a structure’s capacity curve through elastic and rigid plastic analyses. It is validated by comparing the results with those from 420 pushover analyses. Additionally, the method is applied to two case studies designed according to older code provisions, and its accuracy is verified through Incremental dynamic analyses (IDA). The results demonstrate that the simplified method is reliable and provides an accurate evaluation of the structure’s capacity compared to code-based tools.